Embracing Well-Being in Diverse African Contexts: Research Perspectives - Schutte, Lusilda; Guse, Tharina; Wissing, Marié P. (Cross-Cultural Advancements in Positive Psychology, 2022)
XIX, 423 p. 13 illus., 4 illus. in color.